(2x+1) (2x-5) Find the product by suitable property .
Answers
Answered by
1
Answer:
4x² + 2x -5 is ur answer .
Step-by-step explanation:
PLEASE MARK ME AS BRAINLIST
Answered by
2
Answer:
4x² -4x - 5
Step-by-step explanation:
=> (2x + 1)(2x - 5)
=> (2x + 1)(2x + (-5))
We know that, (x + a)(x + b) = (x)² + (a + b)x + ab. . . (i)
where,
- x is the common term in the 2 brackets
- a and b are the variables
Here,
- x => 2x
- a = 1, b = -5
Using the identity (i) :-
=> (2x + 1)(2x - 5) = (2x)² + (1 + [-5])x + 1 x (-5)
= 4x² + (1 - 5)x -5
= 4x² -4x - 5
Similar questions